Aktivnost mišic pri različnih vajah za moč trupa in spodnjih okončin - Andoljšek, Eva (Šport (Ljubljana), 2023)
The purpose of resistance training is to increase muscle performance (muscle strength and power). The activity of a single muscle during different exercises is most easily measured by surface electromyography. In this article, we collected existing review arti- cles comparing the activity of different muscles of the trunk and lower limbs during different exercises. On this basis, we created a graphical overview of selected exercises. Muscle activity during each exercise was expressed as a percentage of activity during the maximum desired isometric contraction. This overview is useful for sports and kinesiology experts, as they can use the article as a guide when selecting appropriate exercises for specific muscles.
Keywords: elektromiografija; mišice; mišična aktivacija; mišična aktivnost; šport; trening moči; vadba proti uporu